Tinjauan Teologis Filosofis Mengenai Pemahaman Tentang Kematian Dan Eskatologi Kristen - Reyna Nurani S; Aprianus Moimau (Jurnal Silih Asuh : Teologi dan Misi, 2024)
Talking about the second coming of the Lord Jesus (eschatology) is one of the foundations of the Christian faith, so this needs to be known, taught and believed by every person of God. However, because there are many interpretations regarding the second coming of the Lord Jesus, correct and appropriate study is needed according to God's word. Lack of understanding regarding the second coming of the Lord Jesus can lead to distorted interpretations that even contradict the truth of God's word itself. There are quite a few errors in the interpretation of the second coming of the Lord Jesus. On the contrary, it causes anxiety, fear, doubt, confusion, and even misdirection. This means that it is very important for us to know more about eschatology, to provide a better and correct understanding in waiting for the second coming of the Lord Jesus. At that time, if we have understood it in a paradigm shift that previously had a frightening perspective, but on the contrary, we are waiting for it with full confidence, a higher level of faith in God and even waiting for it with joy, because He is the one who picks up His people, He is the one who all this time in the world we worship, and also only to Him can we immortalize ourselves completely. Death is human nature and the end of human existence in life. Death is indeed the end of human existence, but humans as physical and spiritual creatures are not completely eliminated by death. The soul/spirit as the spiritual element of humans does not disappear along with the body. The soul is the identity of each human person who reveals the history of his life to God. The human soul will later become a means for God in the process of resurrecting humans. Death is not only something that ends human existence in life, but is also a time when humans perfect/complete the history of their life freely. A life history that shows identity, character, personality, and all the stories that have been experienced that show who he is authentically and finally, without being able to change again. The term human being as both a physical and spiritual creature indicates the unity of the two substances or elements that make up a human being, namely body and soul. This unity, apart from showing the integrity and equality of God's creations, also shows the specialness of humans from other creations. The unity between body and soul as the element that makes humans exist is able to explain the event of the resurrection of the dead which is believed by Christians.